8-сынып оқушыларына «Заттың агрегаттық күйлері» зертханалық жұмысын виртуалды зертхана негізінде оқытудың педагогикалық талдаулары - Жылысбаева, Г.Н.; Жақыпбекова, Г.О. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The article is devoted to the analysis of the advantages and disadvantages of the platforms used in the distance education system of the Republic of Kazakhstan. The most popular distance learning platforms used by teachers and students in schools, colleges and universities, namely such platforms as Zoom, WebEx and Microsoft Teams have been examined. Having analyzed the features of these platforms described in IT-literature, the author came to the conclusion that the most functional platform for conducting online-classes was the Microsoft Teams platform, which was also confirmed by the results of a survey among Karaganda students and schoolchildren. The survey involved 100 people aged 14 to 27 years, most of whom were university students (70 %). At the time of the survey, 85 % of respondents were dissatisfied with the distance learning process, mainly due to the poor Internet connection, as well as the low quality of the educational materials demonstrated by teachers. According to the survey results, the platform Zoom turned out to be the most used platform for distance learning chosen as the leading educational platform by teachers, while the students themselves preferred the Microsoft Teams platform as the most convenient one for online classes due to easy sign-in, the opportunity to save learning materials and other useful services of the platform.
Педагогический анализ изучения лабораторной работы «Агрегатные состояния вещества» для учащихся 8 класса на базе виртуальной лаборатории
Pedagogical analysis of the study of laboratory work “Aggregate states of matter” for 8th grade students on the basis of a virtual laboratory
Keywords: пандемия жағдайында оқыту; химия пəні; қашықтықтан оқыту технологиясы; зертханалық сабақ; виртуалды зертхана; сауалнама əдісі; оқыту əдістемесі; педагогикалық талдаулар